(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Lightweight structures (LWS) or cellular structures have been widely applied in product designs for the aerospace and biomedical industries. Using the advanced additive manufacturing technology, orthopaedic implants can be designed using LWS to achieve low young’s modulus and good bending stiffness, with additional benefits of cell ingrowth if open lattices were designed. In this study, seven patterns of LWS were printed using selective laser melting method. To evaluate the effective young’s modulus as well as the bending stiffness of those LWS, tensile and four-points bending tests were conducted according to the standards of ASTM E8 and F382.